Hydractinia angusta Hartlaub 1904 ... - Peña Cantero, Álvaro L. (Zenodo, 2015)
Hydractinia angusta Hartlaub, 1904 (Fig. 7 A–H) Hydractinia angusta Hartlaub, 1904: 7, pl. 4, figs 1–7; Totton, 1930: 138; Peña Cantero & Ramil, 2006: 950 –951, fig 2; Peña Cantero, 2004: 768; 2014b: 1714. ? Hydronema angustum — Briggs, 1938: 10. Halorhiza angusta — Stechow, 1962: 418. ? Hydractinia angusta — Naumov & Stepanjants, 1972: 33, 35, fig 1; Stepanjants, 1979: 13, pl. 1, fig 7; Cerrano et al., 2000: 488 –493, figs 2–5; 2001: 577–580; Galea & Schories, 2012: 2, pl. 1A–E, fig 2A–C; Peña Cantero et al. 2013: 737 –739, figs 3g –h, 4a–c. Material examined. Belgica Antarctic Expedition 1897–1899: labelled “cotype” (RBINS 539798 INV 38500), (nº 1059), 28.V.1898, 71°19' S, 87°37' W (Bellingshausen Sea), 400 m, c. 22-mm-long colony fragment, with gonophores. Description. Colony growing along three sponge spicules, forming a sort of cylinder of perisarc filled with coenosarc; structure very soft. Polyps white. Gastrozooids and gonozooids present. No dactylozooids. Gastrozooids of varied size ... : Published as part of Peña Cantero, Álvaro L., 2015, Review of some little-known benthic hydroids (Cnidaria, Hydrozoa) from the Southern Ocean, pp. 369-392 in Zootaxa 3972 (3) on pages 380-383, DOI: 10.11646/zootaxa.3972.3.4, http://zenodo.org/record/236731 ...